0532 Defining Sleep Architecture in Pediatric Patients with Prader Willi Syndrome. (25th May 2022) - Patel, Neha; Lew, Jenny; Nino, Gustavo; Weiss, Miriam; Aziz, Julia
Abstract: Introduction: Prader Willi Syndrome (PWS) is a rare genetic disorder characterized by infantile hypotonia, hyperphagia leading to early childhood obesity, and short stature. PWS patients are at risk for multiple sleep abnormalities including increased risk of obstructive sleep apnea, central sleep apnea, and excessive daytime sleepiness. The limited studies reviewing PSGs in pediatric PWS patients showed varying results. Our study aim is to characterize sleep characteristics in pediatric patients with PWS. Methods: We conducted a retrospective chart review of pediatric patients with a genetically confirmed diagnosis of Prader Willi Syndrome from 2007 to 2015. In lab polysomnograms were scored using the AASM criteria for pediatric sleep studies. Data was collected on sleep architecture parameters and compared to normative data available for pediatric polysomnography. Given large variability in sleep architecture during infancy, subjects were divided into two age groups (< 1 years old, 1-19 years old). Results: Fifty-one PSGs were reviewed of which 31 (60.7%) belong to males and 20 (39.3%) belong to females. Forty-one PSGs were initial studies and 11 were repeat studies. Age at the time of sleep study ranged from 11 days to 19 years old. 8 (15%) subjects were less than 1 years old and 44 (84%) were 1 year and older. For subjects less than one year old, mean sleep onset latency (min) was 21±33.4, REM onset latency (min) 35±27.2, SWS(%) 43.3±10.2, REM(%) 35.3±7.35, arousal index 9.7±11.9, wake after sleep onset (WASO) (min) 59.5±11.4 and sleep efficiency 82.4±9.4. For the 1-19 year age group, mean sleep onset latency (min) was 24.5±23.1, REM onset latency (min) 104± 59.9, SWS (%) 21.4±7.11, REM (%) 21.3±6.9, arousal index 7.3±5.4, WASO (min) 46.5±36.10 and sleep efficiency was 85.7±9.0. Conclusion: In our population of PWS patients, REM onset latency was not decreased as shown in previous studies. Sleep efficiency was decreased. Other sleep parameters fell within normal range. Additional data on signs of excessive daytime sleepiness and sleep disordered breathing in this population is needed to understand if EDS persists with decreased sleep efficiency and otherwise normal sleep parameters and/or with OSA. Support (If Any):